2009
DOI: 10.1089/ten.tea.2008.0340
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor–Mediated Signaling in Human Adipose-Derived Stem Cells: Implications for Immunogenicity and Immunosuppressive Potential

Abstract: Human adipose-derived stem cells (hASCs) are mesenchymal stem cells with reduced immunogenicity and the capability to modulate immune responses. These properties make hASCs of special interest as therapeutic agents in the settings of chronic inflammatory and autoimmune diseases. Exogenous and endogenous toll-like receptor (TLR) ligands have been linked with the perpetuation of inflammation in a number of chronic inflammatory diseases such as inflammatory bowel disease and rheumatoid arthritis because of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
137
1
12

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 51 publications
11
137
1
12
Order By: Relevance
“…30,31 Specifically, TLR4-and cytokine-stimulated human MSCs may protect against oxidative stress through activation of antioxidant and anti-inflammatory pathways. 32,33 With respect to effects of TLR ligation on MSCmediated immunosuppression, Lombardo et al found that TLR3 and TLR4 ligation did not affect the ability of adipose-derived stem cells (ASCs) to inhibit T-cell proliferation, nor did TLR ligation change MSC surface HLA-II and costimulatory CD80/CD86 expression. 32 However, using human BMSCs, Liotta et al found that costimulation with TLR3 and TLR4 agonists inhibited MSCmediated suppression by down-regulating Notch ligand Jagged-1.…”
Section: Tlr-mediated Modulation In Human Bmsc Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…30,31 Specifically, TLR4-and cytokine-stimulated human MSCs may protect against oxidative stress through activation of antioxidant and anti-inflammatory pathways. 32,33 With respect to effects of TLR ligation on MSCmediated immunosuppression, Lombardo et al found that TLR3 and TLR4 ligation did not affect the ability of adipose-derived stem cells (ASCs) to inhibit T-cell proliferation, nor did TLR ligation change MSC surface HLA-II and costimulatory CD80/CD86 expression. 32 However, using human BMSCs, Liotta et al found that costimulation with TLR3 and TLR4 agonists inhibited MSCmediated suppression by down-regulating Notch ligand Jagged-1.…”
Section: Tlr-mediated Modulation In Human Bmsc Functionmentioning
confidence: 99%
“…32,33 With respect to effects of TLR ligation on MSCmediated immunosuppression, Lombardo et al found that TLR3 and TLR4 ligation did not affect the ability of adipose-derived stem cells (ASCs) to inhibit T-cell proliferation, nor did TLR ligation change MSC surface HLA-II and costimulatory CD80/CD86 expression. 32 However, using human BMSCs, Liotta et al found that costimulation with TLR3 and TLR4 agonists inhibited MSCmediated suppression by down-regulating Notch ligand Jagged-1. 34 Furthermore, TLR3 and TLR4 activation did not affect MSC induction of IDO and PGE 2 , implying that TLR ligation could restore host defense against viral infections.…”
Section: Tlr-mediated Modulation In Human Bmsc Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst these, TLR3 can recognize double-stranded RNA in viruses and TLR4 can bind to lipopolysaccharide (LPS), a component of Gram-negative bacteria (15,16). Previous studies have demonstrated that TLR3 and TLR4 increase the osteogenic differentiation of MSCs isolated from adipose tissue and bone marrow (17). TLR3 and TLR4 have also been reported to enhance the immunosuppressive properties of human bone marrow-derived MSCS (BM-MSCs) (18).…”
Section: Introductionmentioning
confidence: 99%